2019
DOI: 10.1371/journal.pone.0216076
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies induced by enterotoxigenic Escherichia coli (ETEC) adhesin major structural subunit and minor tip adhesin subunit equivalently inhibit bacteria adherence in vitro

Abstract: Antibodies that block the adherence of enterotoxigenic Escherichia coli (ETEC) to host intestinal epithelial cells are protective. Multiepitope-fusion-antigens (MEFAs) carrying epitopes of ETEC adhesin major subunits or tip minor subunits induced antibodies against ETEC adherence. Adherence inhibition effectiveness of antibodies induced by major subunit epitopes versus minor tip subunit epitopes, however, has not been comparatively characterized. In this study, we immunized mice with a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Also, the serum IgG antibody level was higher in the immunized animals compared to the nonimmunized group, indicating the humoral immunity induction. According to the previous study, subcutaneously immunized mice with these tip subunits alone developed IgG antibody responses to both adhesive subunits [Seo et al, 2019]. Also, there was no significant increase in IgA antibody secretion in comparison with control mice.…”
Section: Discussionmentioning
confidence: 85%
“…Also, the serum IgG antibody level was higher in the immunized animals compared to the nonimmunized group, indicating the humoral immunity induction. According to the previous study, subcutaneously immunized mice with these tip subunits alone developed IgG antibody responses to both adhesive subunits [Seo et al, 2019]. Also, there was no significant increase in IgA antibody secretion in comparison with control mice.…”
Section: Discussionmentioning
confidence: 85%
“…207,208 CFA/I/II/IV MEFA, an epitope-and structure-based recombinant protein carries neutralizing epitope of the seven most important ETEC adhesins (CFA/I, CS1-CS6), induced antibodies that inhibit adherence of ETEC expressing any of these seven adhesins. [209][210][211] Because they are thermostabile and importantly antigenic compatible, 3xSTa N12S -mnLT R192G/L211A and CFA/I/II/ IV MEFA can be combined and co-administered,- 212 leading to the production of a multivalent ETEC subunit vaccine, MecVax. When parenterally (intramuscularly, intradermally, subcutaneously)…”
Section: Etec Subunit Vaccine Candidatesmentioning
confidence: 99%
“…Although more than 20 different ETEC colonization factors have so far been described, the types of ETEC most commonly found associated with childhood diarrhea tend to produce one or more of the seven different colonization factors—colonization factor antigen I (CFA/I) and coli surface antigen 1 (CS1), CS2, CS3, CS4, CS5, and CS6 [ 76 , 81 , 82 , 83 , 84 , 85 ]. Many colonization factors are heteromorphic, filamentous structures called pili or fimbriae, which are usually made up of more than 1000 copies of stalk-forming structural subunits and a single tip adhesin [ 10 , 86 , 87 , 88 ]. Both the structural subunit and the tip adhesin bind to specific targets on the surface of enterocytes.…”
Section: Siga Responses To Etec Infectionmentioning
confidence: 99%
“…For example, both CfaB (structural subunit) and CfaE (tip adhesin) that make up CFA/I bind to glycosphingolipids and glycoproteins on the epithelial cell surface in the small intestine ( Figure 2 d). Studies have also demonstrated that antibodies targeting CfaB and CfaE are able to affect fimbrial elasticity and inhibit adherence of CFA/I-producing bacteria in vitro, respectively, indicating that the colonization factors may be suitable targets for vaccine development [ 10 , 87 , 89 ]. It should also be noted that some colonization factor-specific antibodies may cross-react with other colonization factors [ 90 , 91 ].…”
Section: Siga Responses To Etec Infectionmentioning
confidence: 99%